BH3‐only proteins Noxa, Bik, Bmf, and Bid activate Bax and Bak indirectly when studied in yeast model. Issue 8 (23rd September 2013) - Gérecová, Gabriela; Kopanicová, Jana; Jaká, Petra; Běhalová, Lucia; Juhásová, Barbora; Bhatia‐Kiššová, Ingrid; Forte, Michael; Polčic, Peter; Mentel, Marek
Abstract BH3‐only proteins of the Bcl‐2 family regulate programmed cell death in mammals through activation of multidomain proapoptotic proteins Bax and Bak in response to various proapoptotic stimuli by mechanism that remains under dispute. Here, we report that the cell death‐promoting activity of BH3‐only proteins Bik, Bmf, Noxa, and tBid can only be reconstituted in yeast when both multidomain proapoptotic and antiapoptotic Bcl‐2 family proteins are present. Inability of these proteins to induce cell death in the absence of antiapoptotic proteins suggests that all tested BH3‐only proteins likely activate Bax and Bak indirectly by inhibiting antiapoptotic proteins.